Impact of Exercise on Tramadol-Conditioned Place Preference - Haneen Amawi; Alaa M. Hammad; Aseel Abdullah Ibrahim; Nosyba Alsbih; Frank Scott Hall; Fawaz Alasmari; Bahaa Al-Trad (Brain Sciences)
Background: Tramadol (TRA) is an opioid that is used to manage moderate to severe pain. Long-term use of TRA can lead to the development of opioid use disorder. Objectives: This study investigates the role of forced exercise in reducing TRA-seeking behavior. Methods: Adult male rats (240–260 g) were divided into five groups; the control group received vehicle injections, the TRA group received TRA (75 mg/kg, i.p) every other day for 8 days, and three TRA–exercise groups were forced to run on a treadmill (60 min/day, 5 days/week) for 2, 4, or 6 weeks prior to conditioning with TRA. A tramadol-conditioned place preference (CPP) procedure assessed TRA reinforcement, after which all rats were euthanized, tissue extracted, and mRNA expression for brain-derived neurotrophic factor (Bdnf) and interleukin 1 beta (Il-1β) determined in hippocampus (Hipp), prefrontal cortex (PFC), and nucleus accumbens (NAc). Results: TRA-seeking behavior was seen in the TRA group and the 6 weeks forced exercise group. By contrast, forced exercise for 2 or 4 weeks attenuated TRA-seeking behavior. This attenuation was associated with a significant increase in Bdnf mRNA expression in the Hipp and NAc, but not the PFC. Additionally, the TRA-induced elevations in Il-1β mRNA expression were reversed by all durations of exercise in Hipp. However, only 2 and 4 weeks, but not 6 weeks, of exercise reduced elevations in PFC and NAc Il-1β expression. Conclusion: Forced exercise for 2 and 4 weeks attenuates TRA-seeking behavior partially through the regulation of Bdnf and Il-1β mRNA expression.